Combining Ability in Mixtures of Prairie Grass and Clovers - Arturi, Miguel Jacinto (2012)
Our objective was to evaluate the combining ability among cultivars of forage species, commonly sown in temperate regions of Argentina using a short rotation system. Three genetically diverse cultivars of prairie brome grass (Bromus catharticus, cv Copetona, cv Ñandú and cv Tango), a white clover cultivar (Trifolium repens, cv Lucero) and a red clo-ver cultivar (T. pratense, cv Tropero) were evaluated. A randomized complete block design experiment was established in 2005. The treatments included five monocultures and ten binary mixtures. The experiment was harvested 6 times over an 18-month period. Cumulative dry matter yield (kg·ha–1) was calculated as the sum of the six individual harvests. Diallel analysis provided estimates of the general combining ability (GCA) and specific combining ability (SCA). Red clover in monoculture and mixtures produced the highest yields, with significant positive GCA effects (P < 0.01). Lucero white clover, and Copetona and Tango prairie grasses had significant negative GCA effects (P < 0.05). In mix-tures, red clover with each of the three grass cultivars and white clover with Tango had significant and outstanding SCA effects (P < 0.01). Grass/grass mixtures and the legume/legume mixture showed non-significant SCA effects, while the grass/legume mixtures generally had higher yield than either component sown as a monoculture (P < 0.01). Given the short-term nature of this study, we must limit our inference to short-term pastures (<2 years). Under these conditions, red clover had the best combination with prairie brome grass.